A facile fluorescent sensor based on nitrogen-doped carbon dots derived from Listeria monocytogenes for highly selective and visual detection of iodide and pH. Issue 12 (4th March 2022) - Jie, Mingsha; Guo, Ruipeng; Zhang, Yanan; Huang, Jianing; Xu, Gaigai; Li, Min; Yue, Xiaoyue; Ji, Baocheng; Bai, Yanhong
Abstract : Listeria monocytogenes -derived nitrogen-doped carbon dots served as a facile fluorescent sensor with excellent sensing performances for iodide with low detection limit of 20 nmol L −1 and wide pH range from 1.81 to 11.82. Abstract : Sensitive and visual analysis of iodide (I − ) and pH is significant in environmental and food applications. Herein, we present a facile fluorescent sensor for highly selective and visual detection of I − and pH based on nitrogen-doped carbon dots derived from Listeria monocytogenes (NCDs-LM). The NCDs-LM-based fluorescent sensor showed a good linear relationship to I − concentrations, and the detection limit was calculated as 20 nmol L −1 . The developed sensor was successfully applied to the detection of I − in drinking water and milk samples. Meanwhile, the as-synthesized NCDs-LM sensor can be used to detect pH, achieving a wide linear pH range. Furthermore, fluorescent test papers based on NCDs-LM were designed for semi-quantitative detection of I − and pH via the naked-eye colorimetric assay. The present work indicates that the NCDs-LM-based fluorescent sensor has high potential for use in environmental monitoring and food analysis.